The defect-centric perspective of device and circuit reliability—From gate oxide defects to circuits. (November 2016) - Kaczer, B.; Franco, J.; Weckx, P.; Roussel, Ph.J.; Simicic, M.; Putcha, V.; Bury, E.; Cho, M.; Degraeve, R.; Linten, D.; Groeseneken, G.; Debacker, P.; et al.
Abstract: As-fabricated (time-zero) variability and mean device aging are nowadays routinely considered in circuit simulations and design. Time-dependent variability (reliability-related variability) is an emerging concern that needs to be considered in circuit design as well. This phenomenon in deeply scaled devices can be best understood within the so-called defect-centric picture in terms of an ensemble of individual defects. The properties of gate oxide defects are discussed. It is further shown how in particular the electrical properties can be used to construct time-dependent variability distributions and can be propagated up to transistor-level circuits.